Peranan Penyidik Dalam Penyelesaian Perkara Anak Yang Berhadapan Dengan Hukum (ABH) Melalui Diversi Dengan Cara Restorative justice Di Polres Halmahera Timur - Kurniawan, Muhammad Andy; Teguh Suratman (MLJ Merdeka Law Journal, 2024)
The problem of solving the problem of children facing the law is still interesting to be studied today, the formulation of the problem raised the first What are the factors that support or inhibit investigators in their role to solve cases of children facing the law (ABH) through diversion by way of Restorative justice, the second how the role of East Halmahera police investigators, The research method used is Empirical Legal Research, the results of the first research, from research conducted, supporting factors against the settlement of cases for children who are dealing with the law include the main duties of the National Police as law enforcement under Article 13 of Law No. 2 of 2002 on the Indonesian National Police, states that the National Police has the main, The main task of Satreskrim is to carry out criminal investigations explaining that Satreskrim is in charge of carrying out investigations, investigations, and supervision of criminal investigations, carrying out special service and protection functions for adolescents, children, and women both as perpetrators and victims in accordance with the provisions of the laws and regulations, The main task of the PPA Unit is to provide protection for women and children ,the commitment of the police chief to resolve child cases through diversion,the commitment of investigators to carry out child cases through diversion. While the obstacles faced in the settlement of cases for children who are dealing with the law, namely, in terms of Human Resources , in terms of infrastructure, obstacles to the implementation of diversion against criminal acts committed by children ,in terms of social factors, obstacles to the implementation of criminal acts committed by children also occur because of the factors of the community who do not understand about awareness in law enforcement Restorative justice. The second, from the results of the study the role of East halmahera police investigators in the settlement of child cases dealing with the law (ABH) through diversion by way of Restorative justice , Restorative justice efforts have been made to the maximum in accordance with applicable regulations and procedures that have been in force, although the results of the settlement of cases of ABH cases have not been entirely successful Restorative justice, so that the success rate of settlement of child cases dealing with the law through Restorative justice is 0%. Keywords: The Role Of Investigators, Children Who Face The Law , Diversion, Restorative Justice